2017
DOI: 10.2214/ajr.16.16683
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcomes of Incidental Breast Lesions Detected on Abdominal MRI Over a 7-Year Period

Abstract: Although incidental breast lesions were rarely detected on abdominal MRI, a considerable number of these lesions were found to represent breast cancer, particularly when leading to a recommendation for follow-up breast imaging. Therefore, it is important for radiologists interpreting abdominal MRI examinations to carefully evaluate for the presence of breast abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…In this study, we evaluated the incidence and outcomes of incidental breast lesions that were detected on nonbreast cross‐sectional imaging studies. We found that the incidence and rate of malignancy of incidental breast lesions in our study cohort were overall similar to those reported in previously published studies . However, to our knowledge, there are no previous studies comparing the incidence and outcomes of incidental breast lesions detected on different cross‐sectional imaging studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we evaluated the incidence and outcomes of incidental breast lesions that were detected on nonbreast cross‐sectional imaging studies. We found that the incidence and rate of malignancy of incidental breast lesions in our study cohort were overall similar to those reported in previously published studies . However, to our knowledge, there are no previous studies comparing the incidence and outcomes of incidental breast lesions detected on different cross‐sectional imaging studies.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the incidence and rate of malignancy of incidental breast lesions in our study cohort were overall similar to those reported in previously published studies. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, to our knowledge, there are no previous studies comparing the incidence Another factor that was found to be significantly associated with increased rate of malignancy was patient age, as incidental breast lesions in older patients were significantly more likely to be malignant, which is consistent with the known increase in the risk of breast cancer with age. 17 We found that only 41% of the patients with incidentally Our study has several limitations, one of which is the single-site retrospective design of the study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The challenge of managing incidental findings (IFs) in clinical practice and research is growing with the increasing accessibility of powerful imaging modalities such as MRI [ 1 3 ]. IFs frequently occur in clinical as well as in research settings [ 1 , 2 , 4 ]. The use of whole-body MRI (wb-MRI) in a population-based cohort of 2500 participants resulted in 13,455 IFs, of which 1330 were potentially clinically relevant and disclosed to participants [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 However, data on breast incidental findings on abdominal and chest MRI (MRI-AC) are limited with significant heterogeneity in prior results. [5][6][7] Our goal was to evaluate the frequency of breast incidental findings on MRI-AC, document radiologist recommendations for follow-up diagnostic breast imaging, assess the rate of compliance with follow-up, and identify factors associated with improved follow-up.…”
mentioning
confidence: 99%